Some Aspects of the Chemistry of Hydrazides and Thiohydrazides - Elliot, Arthur (My University, 1971)
In or der to study the mechanism of their conversio~ into hydrazides and thiohydrazides, a number of hydrazidic halides were treated with compounds containing a nucleophilic oxygen or sulfur atom.
The initial products of these reactions were formed from the displacement of the (alpha)-halogen atom of the hydrazidic halide. In cases where there was sufficient activation the group attached to oxygen or sulfur was transferred to nitrogen in the presence of base.
Some hydrazides and thiohydrazides containing displace-able groups in the 2-position of an N-aryl ring yielded benzoxadiazines and benzothiadiazines respectively under basic conditions. The reactions exhibited the characteristics of bimolecular nμcleophilic aromatic substitutions. The synthesis of four novel heterocyclic ring systems is described.
Keywords: conversion, hydrazides, heterocyclic ring systemsthiohydrazides, hydrazidic hallides, nucleophilic oxygen, sulfur atom, alpha halogen, oxygen, base, nitrogen, N-aryl ring, benzoxadiazines, benzothiadiazines, heterocyclic